Review of the book “Capital Penetration and the Peasantry in Southern and Eastern Africa - Neoliberal Restructuring” - Veress Juhaszné, Szilvia (Journal of Central and Eastern European African Studies, 2025)
"Capital Penetration and the Peasantry in Southern and Eastern Africa - Neoliberal Restructuring" is part of the Advances in African Economic, Social and Political Development book series to be published in 2022. The aim of this review is to present the contents of the book and to draw attention to the significance of the essays in the volume. It also aims to provide a brief recommendation for all those experts and researchers who are interested in the evolution, development and problems of agriculture and food security in sub-Saharan Africa.